Text and Subject Position after Althusser - Antony Easthope (Studies in 20th & 21st Century Literature, 1994)
Althusser's achievement is that he redefined Marxism. He reconceptualizes history and totality in terms of different times, construes knowledge as the outcome of a process of construction, and interprets subjectivity as an effect of ideology and unconscious processes. Unfortunately, Althusser's functionalist view of ideology claims that the subject recognizes itself as a subject because it duplicates— reflects—an absolute subject. However, Lacan's notion of the mirror stage remedies this fault. Lacan's subject always misrecognizes itself in a process of contradiction that threatens the stability of any given social order. Moreover, unlike Foucault's subject, which is limited in that subjectivity is folded back into a vaguely expanded notion of "power," this revised Althusserian subject allows careful reading of texts. The critic does not simply read against the grain; he or she exposes the multiple points of identification offered the reader. For example, Wordsworth's "The Solitary Reaper" installs the reader in multiple positions: a devotee of high culture and the national canon, a lover of the verbal signifier and its play, a consumer of confessional discourse, and a masculine "I" desiring a laboring, singing woman.
Keywords: Althusser; marxism; redefined marxism; history; totality; construction; knowledge; time; subjectivity; ideology; unconscious; subject; subject recognizes itself; duplicates; reflect; reflects; absolute subject; mirror stage; Lacan; misrecognizes; itself; self; contradiction; social order; stability; power; Althusserian subject; careful reading; identification; Wordsworth; The Solitary Reaper; high culture; national canon; verbal signifier; masculine I; woman; confessional discourse